2021
DOI: 10.3390/antiox10030491
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Dietary Iron-Chelating Bioactive Compounds in Molecular Mechanisms of Oxidative Stress-Induced Cell Ageing

Abstract: One of the prevailing perceptions regarding the ageing of cells and organisms is the intracellular gradual accumulation of oxidatively damaged macromolecules, leading to the decline of cell and organ function (free radical theory of ageing). This chemically undefined material known as “lipofuscin,” “ceroid,” or “age pigment” is mainly formed through unregulated and nonspecific oxidative modifications of cellular macromolecules that are induced by highly reactive free radicals. A necessary precondition for reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 139 publications
0
25
0
Order By: Relevance
“…Previous studies in primary human fibroblasts and endothelial cells have shown that senescent cells accumulate intracellular iron [ 29 ]; in turn, the presence of intracellular labile iron (Fe(ΙΙ)) is a prerequisite for the development of oxidative stress-induced senescence and apoptosis [ 16 ]. Herein, we show that iron overload leads to oxidative DNA damage in both skin and synovial fibroblasts, suggesting that iron overload may be an additional source of the increased oxidative burden present in fibroblasts isolated from SSc patients [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in primary human fibroblasts and endothelial cells have shown that senescent cells accumulate intracellular iron [ 29 ]; in turn, the presence of intracellular labile iron (Fe(ΙΙ)) is a prerequisite for the development of oxidative stress-induced senescence and apoptosis [ 16 ]. Herein, we show that iron overload leads to oxidative DNA damage in both skin and synovial fibroblasts, suggesting that iron overload may be an additional source of the increased oxidative burden present in fibroblasts isolated from SSc patients [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is not the total amount of iron that is responsible for mediating the oxidative damage, but rather the labile Fe(II) fraction pool that is accessible for interaction with peroxides [ 15 ]. The depletion of intracellular labile iron by exogenous compounds would diminish the formation of damaging ROS and prevent the deleterious over-oxidation of cellular components [ 16 ]. Several lines of evidence suggest that ROS-induced oxidization of lipids and proteins promotes initiation and progression of fibrosis in a variety of organs [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review paper by Barbouti et al [ 17 ], propose that dietary bioactive compounds present in the Mediterranean-type diet protect against oxidative stress-induced cellular ageing by acting as iron chelating compounds, rather than free-radical scavenges. Among several theories that have been proposed to explain the molecular basis of ageing, the so-called “free-radical theory of ageing” [ 18 ], has gained widespread acceptance.…”
mentioning
confidence: 99%
“…In conditions of ongoing oxidative stress, the ability of cells to repair their damaged constituents reach saturation, and over-oxidized non-repairable “waste material” accumulates inside the cells. This chemically undefined material conventionally called “lipofuscin” is a common hallmark of ageing (senescent) cells [ 17 ]. A necessary requirement for the intracellular generation of highly reactive free radicals is the presence of “labile iron” [ 19 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation